Indications for Penile Prosthesis Revision: Lessons Learned to Limit Technical Causes of Reoperation. Issue 9 (11th July 2019) - Chan, Ernest Pang; Punjani, Nahid; Campbell, Jeffrey Douglas; Abed, Haider; Brock, Gerald
ABSTRACT: Introduction: Reoperations are necessary in approximately 30% of penile prostheses over 15 years following original implantation. Aim: To determine the most common indications for initial penile prosthesis reoperation at our institution and to describe technical alterations that have improved postoperative outcomes. Methods: A retrospective review of all patients who underwent penile prosthesis reoperation surgery at a single, high-volume Canadian center between 2006 and 2018 was performed. Patient demographic information, prosthetic device factors, and surgical complications were analyzed. Main Outcome Measure: The primary outcomes were the indications for and variables associated with initial penile prosthesis reoperation. Results: During the study period, 99 first-time penile prosthesis reoperations were performed out of 1, 161 penile prosthesis procedures (Figure 1 ). This included 14 (14.1%) explants, 32 (32.3%) revisions, and 53 (53.5%) explant and reimplants. Indications for reoperation included 49 (49.5%) mechanical failures, 28 (28.3%) technical causes (such as correction of malposition or device herniation), and 12 (12.1%) procedures to treat chronic postoperative pain. Median follow-up was 78.5 months, and median time to reoperation was 46 months. Mechanical failures commonly occurred in the tubing (n = 13, 26.5%) and cylinders (n = 13, 26.5%). The most frequently repositioned component was the valve pump (n = 11, 39.3%). Infection-related indications for reoperation were uncommon (n = 10, 10.1%). Clinical Implications: More than a quarter of penile prosthesis reoperations may have been preventable with alterations in surgical technique, device positioning, and postoperative care. Strengths and Limitations: This study evaluates a range of indications for initial penile prosthesis reoperation performed by a high-volume single surgeon over a 12-year period. Limitations include the retrospective nature of the study, loss of patients to follow-up, and lack of etiological determinants of prosthesis failure. Conclusions: Reoperation for device repositioning and herniation was required for more than a quarter of the initial penile prosthesis implants. Modifications in surgical technique and perioperative care can help reduce the incidence of these technical causes for reoperation.